NK-like CD8+ cells in immunologically naïve neonatal calves that respond to dendritic cells infected with Mycobacterium bovis BCG - Hope, Jayne C.; Sopp, Paul; Howard, Chris J. (Journal of leukocyte biology, 2002)
Pre‐exposure to environmental mycobacteria and induction of an inappropriately biased immune response may be major factors affecting the efficacy of BCG; vaccination of neonates that have not been exposed to environmental mycobacteria may induce more effective immunity. Responses of neonatal calves to mycobacterial antigens using dendritic cells (DC) as antigen‐presenting cells were investigated. In nonvaccinated, immunologically naive calves as young as 1 day old, a population of CD8+ cells proliferated and produced IFN‐γ in response to BCG‐infected DC. CD3− CD8+ NK‐like and CD3+ CD8+ T cells were evident within the responding CD8+ population. The response was not MHC‐restricted. The NK‐like CD3− cells were the major population producing IFN‐γ. The presence of mycobacteria‐reactive, IFN‐γ‐secreting CD8+ NK cells in neonatal calves may have important consequences for the induction of a Th1‐biased immune response.